“Burn through the parochial states of mind”: Dorothy Molloy’s Illness Poetry as a Catalyst for Change (Altre Modernità, 2024)
This article examines how Dorothy Molloy’s poetry inscribes the subjective experience of illness, pain, and female sexuality within ostensibly traditional lyric forms to challenge conventional representations of illness and shed light on the inequities of Celtic Tiger Ireland. The poetic medium is ideally suited to express the painful caesura of infirmity, but Molloy’s poetry also fulfils perlocutive functions that position her cancer poetry as an agent for social change. The aesthetic of the poems collected in the posthumous The Poems of Dorothy Molloy is driven by a socio-political imperative, for the multitude of images depicting debilitated bodies in these verses serves to denounce the problematic perception of terminal diseases and critique the repercussions of entrenched conservative perspectives on the treatment meted out to Molloy and other women in the oncology wards of Irish hospitals during the late 1990s and early 2000s. By adopting an eclectic approach that combines historically-informed close reading with insights from Narrative Medicine, the article shows that Molloy actively seeks an accessible literary form that turns the private experience of illness into public comment and finds it in poetry, which, despite its inherent suitability, demands recalibration. Her verses indicate that prevailing discourses on care in Ireland and much canonical poetic representation of illness necessitate an equivalent degree of adjustment as the medical treatments themselves.